2017
DOI: 10.1371/journal.pone.0176507
|View full text |Cite|
|
Sign up to set email alerts
|

Biosynthesis of the oxygenated diterpene nezukol in the medicinal plant Isodon rubescens is catalyzed by a pair of diterpene synthases

Abstract: Plants produce an immense diversity of natural products (i.e. secondary or specialized metabolites) that offer a rich source of known and potentially new pharmaceuticals and other desirable bioproducts. The Traditional Chinese Medicinal plant Isodon rubescens (Lamiaceae) contains an array of bioactive labdane-related diterpenoid natural products. Of these, the ent-kauranoid oridonin is the most prominent specialized metabolite that has been extensively studied for its potent antimicrobial and anticancer effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…The enzyme activity of the generated protein variants was analyzed in co‐expression assays in an Escherichia coli co‐expression system engineered for enhanced diterpenoid production . The resulting reaction products were readily extracted from the microbial co‐expression cultures in their dephosphorylated form and identified by gas chromatography–mass spectrometry (GC‐MS) through comparison to known enzyme products and, where applicable, by using NMR analysis . Mutation of PvCPS1:F251 to histidine, tyrosine, or leucine—residues of similar size—did not alter product specificity, and the protein variants largely retained wild‐type overall catalytic activity (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme activity of the generated protein variants was analyzed in co‐expression assays in an Escherichia coli co‐expression system engineered for enhanced diterpenoid production . The resulting reaction products were readily extracted from the microbial co‐expression cultures in their dephosphorylated form and identified by gas chromatography–mass spectrometry (GC‐MS) through comparison to known enzyme products and, where applicable, by using NMR analysis . Mutation of PvCPS1:F251 to histidine, tyrosine, or leucine—residues of similar size—did not alter product specificity, and the protein variants largely retained wild‐type overall catalytic activity (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…GC‐MS analysis : Enzyme products formed by microbial co‐expression were extracted directly from the culture with hexane (50 mL), air‐dried and resuspended in hexane (1 mL) for GC‐MS analysis . Extracted products were analyzed on an Agilent 7890B GC interfaced with a 5977 Extractor XL MS detector (70 eV, He flow 1.2 mL min −1 ) by using an Agilent HP5‐ms column (30 m, 250 μm i.d., 0.25 μm film).…”
Section: Methodsmentioning
confidence: 99%
“…Monocot diterpenoids are almost invariably functionally modified by P450 enzymes, with members of the CYP701, CYP71, CYP76 and CYP99 subfamilies having been shown (Harris et al, 2005) or the (+)-CPP synthase, IrTPS3, from Isodon rubescens (Pelot et al, 2017). (c) The GC-MS traces of products resulting from Escherichia coli co-expression assays of SiTPS28 and SiTPS8 with E,E-farnesyl pyrophosphate (FPP) produced by the maize FPP synthase ZmFPPS (Cervantes-Cervantes et al, 2006).…”
Section: Identification Of Sicyp99a17 As a P450 Catalyzing C19hydroxymentioning
confidence: 99%
“…For Isodon species, Li et al [ 18 ] reported the role of two IeCPS genes in ent- copalyl diphosphate synthesis in I. eriocalyx via homologous cloning. Very recently, the diterpene synthases (diTPSs) including CPS and KSL have been identified in I. rubescens [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%